Attention Is Required to Coordinate Reaching and Postural Stability during Upper Limb Movements Generated While Standing. Issue 1 (2nd January 2020) - Dierijck, Jill; Kennefick, Michael; Smirl, Jonathan; Dalton, Brian H.; van Donkelaar, Paul
Abstract: In the present study we investigated how attention contributes to the interaction between reach planning and execution, and postural control. Reaching movements were generated while standing and were performed either in isolation or in conjunction with a secondary reaction time (RT) task. In addition, to better understand how online movement control is affected by this interaction, the reaching movements could be unexpectedly perturbed medial-laterally. Postural kinetic, arm kinematic and RT, and secondary RT measures were used to characterize the responses. Results indicate task performance worsened when both the reaching and secondary tasks were completed simultaneously. Our results imply the generation of reaching movements while standing requires attentional resources to properly coordinate the interaction between the reaching task and postural control.